The combination of papaya seed and orange peel as natural coagulant for greywater treatment - Muhamad, Mimi Suliza; Wan Daruddin, Wan Khairunnisa; Mohd Apandi, Najeeha; Mohamed Sunar, Norshuhaila (2024)
The study utilized a natural coagulant composed of a combination of papaya seed and orange peel to treat greywater. The surface of papaya seed powder was rough and porous, while orange peel powder had an irregular, aggregated structure with non-uniform pores. The papaya seed coagulant was most effective in removing turbidity (86.3%), total suspended solids (50.3%), and chemical oxygen demand (61.4%) at a pH of 7.5, a dosage of 50 mg/L, rapid mixing at 170 RPM for 25 minutes, and slow mixing at 60 RPM for 20 minutes. The orange peel coagulant was most effective in removing 80.5% of turbidity, 64.6% of TSS, and 54.6% of COD at a pH of 7.5, a dosage of 10 mg/L, rapid mixing at 100 RPM for 5 minutes, and slow mixing at 40 RPM for 5 minutes. The ideal conditions for removing turbidity, TSS, and COD with the papaya seed and orange peel coagulant mixture were a pH of 7.5, a dosage ratio of 70:30, rapid mixing at 170 RPM for 25 minutes, and slow mixing at 60 RPM for 20 minutes